The Development of Reason and Its Implications in Religious Learning - Hadini, Hadini; Susanti, Weti; Mujiburrahman, Mujiburrahman; Ichsan, Muhammad; Hayati, Hayati (Al-Hashif: Jurnal Pendidikan dan Pendidikan Islam, 2025)
The Psychological Principle is one of the foundational principles underpinning the implementation of Islamic education. This implies that the execution of education must be based on the developmental stages of the child. In this context, the intellect (reason) as one of the psychological components of human beings is a fundamental element that must be optimized within Islamic education. Although numerous books have discussed the human intellect, very few have explored it from the perspective of its developmental stages. Therefore, an in-depth and comprehensive study of each phase of intellectual development is necessary, so that the formulation of Islamic education can be designed appropriately and contextually. This study employs library research with a qualitative approach. The findings reveal, first, that each phase of human brain development possesses its own characteristics and uniqueness. Second, the research identifies various aspects of Islamic education that align with intellectual development, such as the selection of religious learning materials, instructional approaches, and relevant Islamic educational methods and techniques for each stage of intellectual growth.